Once Weekly Exenatide is Safe and Effective for Long-term T2DM Treatment - Lederman, Lynne (MD Conference Express, 2014)
Patients with type 2 diabetes mellitus (T2DM) require long-term treatment with a hypoglycemic agent, but these agents can be difficult in terms of patient adherence. This article presents 6-year follow-up data on the efficacy of a once-weekly formulation of exenatide. The phase 3 Effects of Exenatide Long-Acting Release on Glucose Control and Safety in Subjects With Type 2 Diabetes Mellitus [DURATION-1; NCT00308139] is the longest assessment of a glucagon-like peptide–1 receptor agonist reported to date.